Influence of blanching and slice thickness on drying characteristics of leek slices - Doymaz, Ibrahim (ELSEVIER SCIENCE SA, 2008)
The effect of blanching and slice thickness on drying characteristics of leek was studied. Drying experiments were performed in a cabinet dryer. Drying time decreased with blanching, but it increased considerably with increased slice thickness of leek. Besides, predrying treatment such as blanching was found to improve the rehydration capacities of leek slices. The experimental drying curves obtained show only a falling rate period. In order to estimate and select the suitable form air drying curves, seven different mathematical models were applied to the experimental data. Determination of coefficient (R-2), reduced chi-square (X-2) and root mean square error (E-RMS) were used for determination of the best suitable model. Among the mathematical models investigated, the logarithmic and Midilli et al. models satisfactorily described the drying behaviour of leek slices with highest R-2 and lowest X-2 and E-RMS. The effective moisture diffusivity during drying varied from 1.145 to 2.642 x 10(-10) m(2)/s. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: leek; drying; blanching; effective moisture diffusivity; mathematical modelling; LAYER; KINETICS; MODEL; PRETREATMENTS; MICROWAVE; QUALITY; LEAVES; CURVE; Energy & Fuels; Engineering